On and off-field behaviour of match officials in professional team sports - Peter Dawson; Patrick Massey; Paul Downward (2021)
The behaviour of referees has been a source of much discussion and debate. The literature has tended to focus on the role of match officials as a source of home bias in association football. Studies reveal discretionary refereeing decisions, such as adding extra time or awarding yellow and red cards, are biased in favour of the home team in Spanish (Buraimo et al., 2012) and German football (Sutter and Kocher, 2004), the English FA Cup (Downward and Jones 2007), The English Premier League (Dawson et al., 2007; Buraimo et al., 2010), as well as the UEFA Champions League (Buraimo et al., 2012). There are also studies of the role of officials in US sports. McCormick and Tollison (1984) examine the increase in officials in Basketball, and Heckelman and Yates (2003) the increase in officials in the National Hockey League. They noted a reduction in fouls called, and no increase in fouls called respectively. The common feature of all the above studies is that they relate to on-field match officials. In other sports, such as in baseball, cricket and rugby, there are mechanisms that enable the on-field referee to use a third-party for assistance in relation to critical decisions. Hamrick and Rasp (2015) report that the monitoring of strike calls in baseball affected umpiring decisions. In 2000 rugby union introduced a television match official (TMO) to help the on-field referee to decide if the ball had been legitimately grounded for a try. In 2013/14, the role was extended to assist in reviewing play immediately before a try. Despite this, referee bias in rugby union has until recently received relatively little attention, although the match officials arguably have a much greater influence on match outcomes than in many other team sports (Page and Page, 2010). Dawson et al. (2019) find in the case of the European Champions Cup the television match official has influenced the incidence of sanctions issued to both teams. However, the increase in the number of yellow cards awarded to away teams implies that home bias increased following the introduction of the television match official. As well as providing an extensive overview of the literature on referee behaviour, this chapter also provides some original insights associated with the Pro-14 rugby competition.